Cadets' Perception in English Online Learning during Covid - 19 Pandemic - Sunarlia Limbong (AL-ISHLAH: Jurnal Pendidikan, 2021)
Indonesia has implemented online learning as part of its education reforms in an effort to contain the spread of the Covid – 19 virus. Study participants' perceptions of online learning during the Covid-19 pandemic are examined in this research. It was a descriptive quantitative study. Questionnaires (Google forms) and in-depth interviews were used to collect data. One hundred fifty-five cadets responded to the survey. Covid–19 pandemic showed that the cadets had an excellent view of online learning. Amid this pandemic, they discovered that online learning was helpful but not entirely efficient. Online learning by lecturers was effective, efficient, varied, helped cadets understand the material, independent learning, and increased students' involvement in learning activities. Additionally, this study gathered information from students in the form of constructive feedback on how to improve online learning. Covid – 19 pandemic cadets also discovered a number of obstacles related to online learning, such as barriers to students' accessing online learning platforms. In the context of the Covid-19 pandemic, the need for further research into the extent of the digital divide is necessitated by this study.